Proteomic analyses of urinary exosomes identify novel potential biomarkers for early diagnosis of sickle cell nephropathy, a sex-based study - Packialakshmi, Balamurugan; Limerick, Emily; Ackerman, Hans C.; Lin, Xionghao; Nekhai, Sergei; Oliver, James D.; Stewart, Ian J.; Knepper, Mark A.; Fitzhugh, Courtney; Zhou, Xiaoming (Frontiers in Physiology, 2024)
Sickle cell nephropathy (SCN) is a leading cause of morbidity and mortality in sickle cell disease (SCD). Early intervention is crucial for mitigating its effects. However, current diagnostic methods rely on generic tests and may not detect SCN until irreversible renal damage occurs. Therefore, specific biomarkers for early diagnosis of SCN are needed. Urinary exosomes, membrane-bound vesicles secreted by renal podocytes and epithelial cells, contain both common and cell type-specific membrane and cytosolic proteins, reflecting the physiologic and pathophysiologic states of the kidney. Using proteomics, we analyzed the proteomes of urinary exosomes from humanized SCD mice at 2 months (without albuminuria) and 4 months (with albuminuria) of age. Excretion of 164 proteins were significantly increased and 176 proteins was significantly decreased in the exosomes when mice developed albuminuria. Based on the relevance to SCD, chronic kidney disease and Western blot confirmation in mice, we analyzed protein abundance of heparanase, cathepsin C, α2-macroglobulin and sarcoplasmic endoplasmic Ca2+ ATPase-3 (SERCA3) in the urinary exosomes and urine of 18 SCD subjects without albuminuria and 12 subjects with albuminuria using Western blot analyses. Both male and female subjects increased or tended to increase the excretion of these proteins in their urinary exosomes upon developing albuminuria, but female subjects demonstrated stronger correlations between the excretion of these proteins and urine albumin creatinine ratio (UACR) compared to male subjects. In contrast, exosomal excretion of Tamm-Horsfall protein, β-actin and SHP-1 was independent of albuminuria. These findings provide a foundation for a time-course study to determine whether increases in the levels of these proteins precede the onset of albuminuria in patients, which will help determine the potential of these proteins as biomarkers for early detection of SCN.